Wacana Purifikasi dalam Tafsir Pendidikan Guru Agama: Analisis Ideologis Terhadap Penafsiran Peladjaran Tafsir Qurän - Moh Muhyiddin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Religious discourse in Indonesia is the result of complex interactions between religious texts and diverse local cultures. However, in the last two decades, there have been efforts to reject the practice of local culture in religion. These efforts have been carried out and disseminated through formal and non-formal education, preaching, interpretation, and educational books. One educational book that is suspected of promoting purification discourse is Peladjaran Tafsir Qurän (Quranic Interpretation Lessons). This book is used as a reference for teachers and students in religious teacher training schools. This is an interesting topic to explore because the interpretation literature in PGA and the ideology in the book have not yet been exposed. This research is a library research using content analysis of selected verses in the Qur'anic interpretation lessons. By analyzing Surah Yunus verse 106 and Al-Maidah verse 3 in three books of Peladjaran Tafsir Qurän, respectively by H.M.K. Bakry and M. Nur Idris, and M. Nur Idris, H.M.K. Bakry and Drs. Gazali Dunia, the conclusion that can be drawn is that the interpretations in the Qur'anic Exegesis lessons contain modernist Islamic ideology in the literature of Religious Teacher Education. The authors of the interpretations sought to criticize traditional Islamic practices in society, such as visiting and praying at the graves of wali, decorating graves, and slaughtering animals in the name of aulia. These behaviors were considered blind imitation, bid'ah, khurafat, and shirk.